Comparative evaluation of total phenolics, total flavonoids and antioxidant capacity of dried shrimp and fermented shrimp products - Kaida, S. T.; Rahmat, A.; Ramli, Nurul Shazini (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
The planktonic shrimp (Acetes indicus) is known as ‘geragau’ by local people in Malaysia. The fermented shrimp products, ‘belacan’ (shrimp paste) and ‘cincalok’ (fermented shrimp sauce) have attracted considerable attention due to their delicacy. The present work aimed to compare total phenolic content, total flavonoid content and antioxidant capacity of dried shrimp and its fermented products, ‘belacan’ and ‘cincalok’. Total phenolic (TPC) and flavanoid content (TFC) were determined using Folin-ciocalteu and aluminium trichloride colorimetric method respectively. Antioxidant capacity were determined using beta-carotene bleaching method and 2,2-diphenyl-1-picylhydrazyl (DPPH) radical scavenging assay. Results showed that fermented shrimp products (‘belacan’ and ‘cincalok’) had higher TPC content (p<0.05) compared to dried shrimp. However, ‘cincalok’ had the highest TFC and antioxidant capacity followed by ‘belacan’ and dried shrimp (p<0.05). The present study suggested that fermented shrimp products exhibited excellent antioxidant capacity compared to dried shrimp which might be due the preservation of the bioactive compounds and/or production of new antioxidant compounds during the fermentation process of ‘belacan’ and ‘cincalok’.